Fluidity of Pure Aluminum in a Narrow Channel Die Gap during Die Casting - Toshio Haga; Hiroshi Fuse (Metals, 2024)
Fluidity tests of 99.9%Al and 99.7%Al were conducted using a die casting machine equipped with a spiral die with a channel gap of 0.5 mm. The effects of die temperature and plunger speed on the fluidity were investigated. To clarify the flow length for these alloys, ADC12 and Al-X%Fe (X ≤ 1.1) were also cast. A 1.0 mm channel gap was also used to compare the fluidity in a wider gap. The fluidity of 99.9%Al and 99.7%Al at a die temperature of 30 °C and a plunger speed of 0.2 m/s was superior to that at 150 °C and 0.8 m/s when the channel gap was 0.5 mm, and similar results were found for ADC12 and Al-X%Fe. When the die temperature was 30 °C, the fluidity of 99.9%Al and 99.7%Al decreased as the plunger speed increased when the channel gap was 0.5 mm, and similar results were also found for ADC12 and Al-X%Fe. These results did not align with conventional expectations. A discussion of the results based on the peeling and re-melting of the solidified layer was provided.